1992
DOI: 10.1080/07315724.1992.10718232
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged tube feeding in long-term care: nutritional status and clinical outcomes.

Abstract: This study examines nutritional status and clinical outcomes, including pressure ulcers and death in 40 chronically tube-fed long-term care patients. Anthropometric, biochemical, clinical and dietary data were collected over a 3-month period, with follow-up of mortality at 1 year. Subjects' functional and cognitive status was generally poor. Adequate calories and protein were provided, with sample means exceeding standard means for energy, protein and micronutrients. Still, subjects showed weight loss and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 26 publications
1
43
1
3
Order By: Relevance
“…Tube feeding is very common among these patients for three main reasons: it avoids undernutrition, it prevents broncho-aspiration with the corresponding risk of pneumonia, and it prolongs survival. Numerous studies have shown that artificial feeding does not improve nutritional parameters or avoid nutritional worsening in patients with advanced dementia (Henderson et al, 1992;Finucane et al, 1999;Dharmarajan et al, 2001;Kim, 2001), data with which our results agree. However, our data do not agree with those studies reporting fewer respiratory infections in patients with NGT.…”
Section: Discussionsupporting
confidence: 93%
“…Tube feeding is very common among these patients for three main reasons: it avoids undernutrition, it prevents broncho-aspiration with the corresponding risk of pneumonia, and it prolongs survival. Numerous studies have shown that artificial feeding does not improve nutritional parameters or avoid nutritional worsening in patients with advanced dementia (Henderson et al, 1992;Finucane et al, 1999;Dharmarajan et al, 2001;Kim, 2001), data with which our results agree. However, our data do not agree with those studies reporting fewer respiratory infections in patients with NGT.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with severe neurological deficits and functional impairment do not do well even when provided with adequate calories and nutrients through enteral feeding [20,21]. In cases of lean body mass and weight decline, these patients develop a number of complications including decubiti; an impairment of the ability to synthesize protein [20] may be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of lean body mass and weight decline, these patients develop a number of complications including decubiti; an impairment of the ability to synthesize protein [20] may be responsible. We believe our study population presents striking similarities with the patients in these studies and have termed this constellation the ''failure to thrive syndrome of advanced dementia.''…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Henderson and colleagues identified that longer-term tube feeding was actually associated with weight loss. 10 These complex ethical and legal dilemmas have been highlighted recently with the publication of new practical guidance from the Royal College of Physicians. 11 A reduced number of patients with advanced dementia alone undergoing PEG insertion was demonstrated in our unit following the introduction of preassessment.…”
Section: Discussionmentioning
confidence: 99%